Preliminary Reflection on Basic Principle of Operation Management for Public Work Infrastructure Asset Management - Ria Asih Soemitro; Hitapriya Suprayitno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Public Works Infrastructure is vital for the life of a region. Therefore, it needs to be well operated. The knowledge or science of Operation Management is well developed, mainly for a Production Entreprises. The operation of infrastructure is different from those of the production enterprise. Therefore the Basic Principle of Operation Management for Public Works Infrastructure needs to be developed. Based on the system analysis principle, several findings have been produced. The infrastructure operation system consists of different system components. The infrastructure form, the infrastructure function, and the infrastructure operation characteristics, together, form the operation mechanism. The operation management manages the operation mechanism to achieve a certain level of operating performance measure. The infrastructure main function can be divided into to serve the user in the region or to produce something for the region. The function to serve can be of three basic forms: to flow something, to be used (in sense of to occupy at a certain time) by the users, or to be used for certain interactive activities. Regarding the variety of the nature of the infrastructure forms, functions, and operation characteristics, the infrastructure operation mechanism is also varied a lot in nature. Thus the operation management will be different for different types of infrastructures.